2011
DOI: 10.1016/j.bcp.2011.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Exploring behavioral and molecular mechanisms of nicotine reward in adolescent mice

Abstract: Tobacco smoking during adolescence has become a prominent preventable health problem faced in the United States. Addictive properties of smoking are thought to have a pronounced effect at a young age, thereby increasing vulnerability to a life-long addiction and decreasing the likelihood of smoking cessation during adulthood. Learning and memory involvement in nicotine reward was assessed in early adolescent (PND 28–34) and adult (PND 70+) male ICR mice by conducting conditioning sessions of nicotine (0.5 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Accordingly, adolescents demonstrate greater reinstatement of conditioned place preference for drugs of abuse [43, 44]. VTA dopamine neurons, through their projections to ventral striatum and prefrontal cortex, play a critical role in value learning, attention and working memory [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, adolescents demonstrate greater reinstatement of conditioned place preference for drugs of abuse [43, 44]. VTA dopamine neurons, through their projections to ventral striatum and prefrontal cortex, play a critical role in value learning, attention and working memory [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Converging evidence from a number of sources has led to the suggestion that elevations in D1R expression in frontal cortex may impart a vulnerability for drug-associated cues, while also contributing to adolescent-motivated behaviors (Brenhouse and Andersen, 2008; Brenhouse et al, 2008; Kota et al, 2011; Leslie et al, 2004). One recent approach providing data consistent with the suggestion of an involvement of D1Rs in expression of adolescent-typical behaviors comes from work assessing consequences of lentivirus-induced overexpression of D1Rs in the prelimbic PFC of adult rats.…”
Section: The Neurobiology Of Rewards and Aversions During Adolescencementioning
confidence: 99%
“…No drugs are administered on testing days and time spent in the prior drug-paired side indicates higher rewarding properties of the drug (Tzschentke, 1998). Kota et al (2011) examined differences between adolescent (P28–36) and adult (P70) ICR mice using three drug pairings at 5 different doses. It was found that adolescent mice conditioned with nicotine acquired CPP at 0.05mg/kg, 0.1mg/kg, and 0.5 mg/kg compared to saline controls.…”
Section: Adolescent Nicotinementioning
confidence: 99%